2007
DOI: 10.1182/blood.v110.11.2346.2346
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Refractory Diffuse Large B-Cell Lymphomas (DLBCL) Are Effectively Killed by Ofatumumab-Induced Complement-Mediated Cytoxicity.

Abstract: The combination of chimeric CD20 monoclonal antibody (mAb) rituximab (R) with chemotherapy (CHOP) has significantly improved clinical outcome in patients with diffuse large B-cell lymphoma (DLBCL). However, the efficacy of R-CHOP is variable and DLBCL remains fatal in 30–40% of the patients. We recently developed the novel fully human CD20 mAb, ofatumumab (2F2) that is currently in clinical development for CLL and follicular lymphoma (phase III) and rheumatoid arthritis (phase II). In this study, we compared o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…(Teeling et al , ) In vitro studies demonstrated that ofatumumab effectively induces complement‐dependent cytotoxicity of chemotherapy‐refractory DLBCL cells. (Cillessen et al , ) Ofatumumab is approved for the treatment of patients with chronic lymphocytic leukaemia refractory to fludarabine and alemtuzumab and is currently in development for the treatment of NHL and other haematological malignancies. (Wierda et al , ; Czuczman et al , ,b) The present study was designed to investigate the efficacy and safety of single‐agent ofatumumab in patients with relapsed/progressive DLBCL who were ineligible for ASCT or who had relapse/progression after ASCT.…”
mentioning
confidence: 99%
“…(Teeling et al , ) In vitro studies demonstrated that ofatumumab effectively induces complement‐dependent cytotoxicity of chemotherapy‐refractory DLBCL cells. (Cillessen et al , ) Ofatumumab is approved for the treatment of patients with chronic lymphocytic leukaemia refractory to fludarabine and alemtuzumab and is currently in development for the treatment of NHL and other haematological malignancies. (Wierda et al , ; Czuczman et al , ,b) The present study was designed to investigate the efficacy and safety of single‐agent ofatumumab in patients with relapsed/progressive DLBCL who were ineligible for ASCT or who had relapse/progression after ASCT.…”
mentioning
confidence: 99%
“…145 Regarding ADCC, most data demonstrate relative equivalence between rituximab and ofatumumab, though some studies suggest that ofatumumab displays greater efficacy in this modality also.- 146,147 Preclinical studies of ofatumumab demonstrated superior in vitro activity in comparison to rituximab providing justification for further clinical trials. 146,148 Indolent hematological malignancies…”
Section: Ofatumumabmentioning
confidence: 99%
“…While these agents have not been specifically tested in DHL a number are proving promising in relapsed or refractory DLBCL more generally. Approaches currently being explored include optimized anti-CD20 antibodies [Cillessen et al 2007; Morschhauser et al 2013], anti CD40 antibodies [Advani et al 2006], anti-PD1 monoclonal antibodies [ClinicalTrials.gov identifier: NCT02362997] and vascular endothelial growth factor (VEGF) antibodies [Willett et al 2004; Stopeck et al 2012]. In the search for efficacy, some monoclonal antibodies have been conjugated to a variety of drugs and radioactive molecules [Bartlett et al 2013; Advani et al 2010; Ribrag et al 2014; Morschhauser et al 2004].…”
Section: Improving Prognosis In Dhl: Incremental Versus Paradigm Shiftsmentioning
confidence: 99%